Biopolítica e educação: desafios da inclusão escolar das pessoas com deficiência no neoliberalismo - Matos, Maria Angélica Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The present research aims to bring a reflection, by the means of the Philosophy of Education, about the challenges of including the person with disabilities in the context of neoliberal biopolitics. It is a study based on the genealogical method, used by the French philosopher Michel Foucault, in which, when concerned with the formation of the subject in the present, questions the prevailing discourse of truth and its relationship with the production of knowledge-power. Through Foucauldian studies, we tried to understand how inclusion started to exist in modernity, passing through classical liberalism, which understood deficiencies as a social risk, basing its biopolitical strategy on disciplinary devices, by isolation in institutions such as the church, prison, etc. Subsequently, with neoliberalism, the strategies of security devices emerged, consisting in maximally capturing deviations, in order to normalize the management of life to the point that this life plays a role in the labor market. Thus, it was necessary to understand who these current inclusion subjects are, highlighting their difference as a people who refuse to be part of the population, due to accidental issues present in the condition of having a disability. In this sense, we tried to problematize the current inclusion policies, starting with the Salamanca Declaration and the most recent National Special Education Policy from the perspective of Inclusive Education. These policies, although they have a lot to contribute with a positive idea of power, by opening spaces for thinking about inclusion in the common school and by bringing people with disabilities together with other students considered “normal”, also bring other modes of exclusion underway. When perceived that in both policies, the specialized scientific bias anchors the main inclusion practices, it is possible to perceive the examining and deciphering role, placing the disabled person as an object-subject to be corrected, since the specialist's main function is to seek the specific deficiencies through the report, in order to understand the person only by what he presents in the disability, and no more than that. It implied thinking that the success of the current inclusion is in making the deficiency less apparent as possible by means of normalizing devices, which also nullify the part in which the deficiency expresses in the subject what is excluded from the normal and allow another dimension of thinking about oneself, and can make a difference that leads to other processes of subjectification. This policy weakens a biopolitics of life, because in times of reflux of State policies, market disputes intensify and place these subjects in unequal conditions, to the point of living on their own. Therefore, we try to think that this path proposed by Special Education still faces enormous challenges in the present, as it demands from the school actors a posture of welcoming these lives, as a way of making them, through their experience, their powers, able to produce a policy that fits their lives, as it is, at school and beyond. In other words, it is about producing an ethics that welcomes differences.

A presente pesquisa tem por objetivo refletir, por intermédio da Filosofia da Educação, acerca dos desafios de incluir a pessoa com deficiência no contexto da biopolítica neoliberal. Trata-se de um estudo baseado no método genealógico, utilizado pelo filósofo francês Michel Foucault, no qual, ao se preocupar com a formação do sujeito no presente, questiona o discurso de verdade em circulação e sua relação com a produção do saber-poder. Através dos estudos foucaultianos, procurou-se compreender de que modo a inclusão começou a existir na modernidade, passando pelo liberalismo clássico, que compreendia as deficiências como um risco social, baseando sua estratégia biopolítica nos dispositivos disciplinares, através do isolando em instituições como a igreja, prisão, etc. Posteriormente, com o neoliberalismo emergiram as estratégias dos dispositivos de segurança, que consiste em capturar ao máximo os desvios, de modo a normalizar o governo da vida a ponto dessa vida desempenhar uma função no mercado de trabalho. Desse modo, foi preciso compreender quem são esses sujeitos da inclusão atual, destacando sua diferença como povo que se recusa fazer parte da população, pelas questões acidentais presentes na condição de ter deficiência. Nesse sentido, procurou-se problematizar as políticas de Inclusão atual, começando pela Declaração de Salamanca e a mais recente Política Nacional de Educação Especial na Perspectiva da Educação Inclusiva. Essas políticas, embora em muito tem a contribuir com uma ideia positiva de poder, ao abrir brechas de se pensar a inclusão na escola comum, juntando as pessoas com deficiência aos demais alunos tidos como “normais”, há outros modos de exclusão em curso. Quando percebido que em ambas políticas, o viés científico especializado ancora as principais práticas de inclusão, foi possível perceber seu papel examinador e decifrador, colocando a pessoa com deficiência como sujeito-objeto a ser corrigido, pois a principal função do especialista é buscar as especificidades das deficiências através do laudo, de modo a entender a pessoa apenas pelo que ela se apresenta com a deficiência, e não mais que isso. Implicou-se pensar que o sucesso da inclusão atual está em tornar a deficiência menos aparente possível por meio dos dispositivos normalizadores, de forma a anular uma parte em que essa deficiência expressa no sujeito não a marca de algo a ser corrigido, mas aquilo escapa e permite uma outra dimensão de se pensar a si mesmo e marcar uma diferença que leve a outros processos de subjetivação. Essa política fragiliza uma biopolítica da vida, pois em tempos de refluxo das políticas do Estado, as disputas do mercado se acirram e colocam esses sujeitos em condições desiguais, a ponto de viverem à própria sorte. Portanto, buscamos pensar que esse caminho proposto pela Educação Especial ainda perpassa por enormes desafios no presente, pois exige dos atores da escola uma postura de acolhimento dessas vidas, como forma de fazer com que eles próprios, pela sua experiência, pelas suas potências, possam produzir uma política que caiba suas vidas, tal como é, na escola e fora dela. Em outras palavras, trata-se da produção de uma ética que acolha as diferenças.
Biopolitics and education: challenges in school inclusion of people with disabilties in the neoliberalism
Keywords: School inclusion; Disability; Challenge; Neoliberal biopolitics; Inclusão escolar; Deficiência; Desafios; Biopolítica neoliberal